2004
DOI: 10.1081/ja-120030893
|View full text |Cite
|
Sign up to set email alerts
|

Violence Related Injuries in the Emergency Room: Alcohol, Depression, and Conduct Problems

Abstract: In the city of Pachuca, Mexico, a large relationship between drinking prior to the event and violence-related injury, regardless of alcohol dependence, was found. Depression was also related to violence, suggesting the need for more comprehensive intervention with these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
7
17
0
4
Order By: Relevance
“…If subjects decided to drink, increased amounts may have pronounced consequences in their risk for triggering an injury, specially a violence-related injury. This work confirms prior reports in Argentina, 15,16 Brazil 17-21 and Mexico 7,12,22 showing the impact of alcohol consumption on violence. Alcohol was present in almost 50% of all patients with a violence-related injury, substantiating a common view in EDs across the region that alcohol consumption is a main problem among these patients.…”
Section: Discussionsupporting
confidence: 81%
“…If subjects decided to drink, increased amounts may have pronounced consequences in their risk for triggering an injury, specially a violence-related injury. This work confirms prior reports in Argentina, 15,16 Brazil 17-21 and Mexico 7,12,22 showing the impact of alcohol consumption on violence. Alcohol was present in almost 50% of all patients with a violence-related injury, substantiating a common view in EDs across the region that alcohol consumption is a main problem among these patients.…”
Section: Discussionsupporting
confidence: 81%
“…Vinson et al 20 showed in case-control and case-crossover analyses that odds ratios for violence-related injuries are especially high when the injury is associ--ated with alcohol use during the 6 hours prior to injury (OR = 34; 95% CI = 4.7-250); this finding has been reported by others 6,36,44,45 and confirmed by this research. The risk of suicide attempts was especially high in our study, confirming a more limited finding from a frequency analysis of a case-crossover study in a sample of patients from Australia, Canada, Mexico and the United States 46 as well as a study in Texas 47 and a hospital-based case-control study in Mexico City.…”
Section: Research Guilherme Borges Et Al Alcohol Use and Injuries Trsupporting
confidence: 77%
“…5 A previous analysis by our group, using data only from Mexico, did not find an increase in the risk of injury when consuming only one drink 6 hours before an injury was compared with alcohol use during the same time period the day prior to or the month prior to the injury. 36 Some reports have tried to disen--tangle differences between acute alcohol use and risk of injury according to the participant's usual consumption pat--tern; 17 this is a matter of great interest to public health professionals. 37 Studies of drivers involved in fatal crashes 19 and cross-sectional data from a study of drinking and driving, 38 as well as data from population surveys of drinking and injury, 39 have suggested that episodes of intoxication may have a different im--pact among people who do not usually drink heavily.…”
Section: Main Findingsmentioning
confidence: 99%
“…Prevalence distinctions among studies can be caused by different measuring tools used or different definitions of mental health problems. In the Borges et al [40] study, the percentage of people categorized in the most serious depression quartile was 16.8. In that study, depressed mood was measured by the Center for Epidemiologic Studies Depression Scale (CES-D), which was used for assessing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%